The prevalence and antimicrobial resistance of Pseudomonas species in patients with chronic suppurative otitis media - AL-Ataar, Zaid I. (AL-Kindy College Medical Journal, 2015)
Background: Chronic suppurative otitis media (CSOM) is the result of an initial episode of acute otitis media and is characterized by a persistent discharge from the middle ear through a tympanic perforation for at least 2 weeks duration. It is an important cause of preventable hearing loss, particularly in the developing world.Objective: To get an overview on the bacterial ear infection profile in general and to assess the antibiotic resistance of Pseudomonal infection (PS) particularly since it is usually the commonest infection to cause otitis media and the most difficult to treat due to the problem of multi drug resistance..Methods: A cross sectional study was done which included 405 patients of CSOM patients, 196 (48%) case were males, 209 (52%) case were females. Swabs for aural discharge were taken from those patients. Discharge is cultured by inoculating it into blood, Mac Conkey agar, chocolate agars and Sabouraud agar (for fungi).If the isolate shows to be Pseudomonas isolate growth then another culture of the isolate is performed on Muller Hinton Agar. Then the antibiotic susceptibility and resistance of Pseudomonas isolate is assessed by (Kirby-Bauer Method)Results: 196 (48%) case were males, 209 (52%) case were females with a male to female ratio 1:1. One hundred fifteen(73%) cases were infected with Pseudomonas species (PS).The sensitivity of the Pseudomonas isolates to the followingantibiotics was Amikacin 91.7%, Imipenem 89.7%, Ceftazidime 81.8%, Ciprofloxacin 73.7%, Garamycin 72.9%, Tobramycin 67.7%, Ticarcillin 66.7%,Cefoperazone 42.9%Conclusion: Pseudomonas species is the commonest microorganism in cases of CSOM. Microbiological identifications and antibiotic resistance determination of pathogens isolated from the middle ear in patients with CSOM not responding to empirical antibiotic treatment gives possibility of the choice of an effective antibiotic and its proper dosage. Cefoperazone , a relatively new antibiotic that is used in Iraq to combat pseudomonal infections has proven to be poorly effective compared with other previously used antibiotics